A simple adjustment to test reliability of bacterivory rates derived from the dilution method. (28th October 2015) - Pree, Bernadette; Kuhlisch, Constanze; Pohnert, Georg; Sazhin, Andrey F.; Jakobsen, Hans Henrik; Lund Paulsen, Maria; Frischer, Marc E.; Stoecker, Diane; Nejstgaard, Jens C.; Larsen, Aud
Abstract: Quantification of grazing losses of marine heterotrophic bacteria is critical for understanding nutrient and carbon pathways in aquatic systems. The dilution method is a commonly used experimental approach for quantifying bacterivory. However, valid estimates of grazing rates obtained using this method depend on several methodological assumptions including that the method does not influence specific growth rates of bacteria. Here, we hypothesize that filtration during the set‐up of a dilution experiment has the potential to release allelochemicals from phytoplankton cells and thereby stimulate or inhibit bacterial growth with the consequence of biased grazing estimates. We tested this hypothesis during a natural Phaeocystis pouchetii bloom at two different locations within an Arctic fjord. Results from the dilution experiments suggest higher gross growth rate and grazing impact for bacteria in the outer fjord compared with the inner fjord. However, specific growth rates estimated by bacterial production cell −1 were significantly elevated in dilutions of water from the outer fjord but not the inner fjord. The analysis of dissolved metabolites in the seawater from both experiments prior and after filtration revealed altered metabolic profiles after filtration at both stations. As unaffected specific growth of prey on dilution is one of three fundamental assumptions of the dilution method, we conclude that it is important that empirically estimated bacterial specific growth rates be routinely included when using the dilution method to quantify bacterivory.